WHERE ARE YOU GOING, CPA? - Byrnes, Thomas W. (The Accounting Review, 1953)
Abstract Mergers give the concept of big business. The combining of accounting firms of moderate size with others to become a nationally known organization can lead certified public accountants away from professional status. In the mind of the layman, the practitioner of a profession is one who gives personal attention to the intimate affairs of a client or a patient, and although some actual service may, as in the case of public accountants, be delegated to staff assistants, yet the client of the smaller firm is acquainted with, and feels he has the personal interest of, one of the principals. It may be said that the same relationship can be continued under the new firm name, and it is true there are clients who may like the idea of the larger organization, but there are a great many persons who do not desire information concerning their private affairs to be in the flies of a widespread copartnership. Public accounting has come a long way in the past fifty years and enjoys a well earned high place in the public esteem, but if big business with all that description connotes, is the aim of many of its practitioners, then all pretense to professional rating should be dropped. Merely to state that a vocation is a profession does not make it such. Actions speak louder than words.